Inventory of Protective Trees on Campus I of Universitas Negeri Padang - Deguci, A. Rivo (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2023)
Protective trees are plants with tall trunks, broad leaves, and extensive canopies. Universitas Negeri Padang (UNP) is a leading university in West Sumatra, aiming to become the best university at both national and international levels. To achieve this goal, UNP has implemented policies to expand or improve its infrastructure to support education. However, this has led to a decrease in the presence of protective trees due to continuous land use. This research aims to identify the types, distribution, and quantity of protective trees on Campus I of Universitas Negeri Padang. The study was conducted in June-July 2023 using a descriptive approach with the cruise method. Data obtained from the research were analyzed descriptively and presented in the form of tables, images, and mapping. The results reveal the presence of 37 types of protective trees from 19 families. Syzygium myrtifolium Walp. (Red Shoot) is the most commonly found protective tree, with 935 trees scattered throughout the faculties